Simulating the interaction of jets with the intracluster medium - Weinberger, Rainer; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2017)
Jets from supermassive black holes in the centres of galaxy clusters are a potential candidate for moderating gas cooling and subsequent star formation through depositing energy in the intracluster gas. In this work, we simulate the jet-intracluster medium interaction using the moving-mesh magnetohydrodynamics code arepo. Our model injects supersonic, low-density, collimated and magnetized outflows in cluster centres, which are then stopped by the surrounding gas, thermalize and inflate low-density cavities filled with cosmic rays. We perform high-resolution, non-radiative simulations of the lobe creation, expansion and disruption, and find that its dynamical evolution is in qualitative agreement with simulations of idealized low-density cavities that are dominated by a large-scale Rayleigh-Taylor instability. The buoyant rising of the lobe does not create energetically significant small-scale chaotic motion in a volume-filling fashion, but rather a systematic upward motion in the wake of the lobe and a corresponding back-flow antiparallel to it. We find that, overall, 50 per cent of the injected energy ends up in material that is not part of the lobe, and about 25 per cent remains in the inner 100 kpc. We conclude that jet-inflated, buoyantly rising cavities drive systematic gas motions that play an important role in heating the central regions, while mixing of lobe material is subdominant. Encouragingly, the main mechanisms responsible for this energy deposition can be modelled already at resolutions within reach in future, high-resolution cosmological simulations of galaxy clusters.